THE EFFECT OF GLOBAL METHOD ON STUDENTS READING COMPREHENSION OF THE NINTH GRADE STUDENTS AT STATE ISLAMIC JUNIOR HIGH SCHOOL (MADRASAH TSANAWIYAH NEGERI/MTsN) 5 AT JAMBI CITY - MASLAHAH, INDAH (JR-ELT (Journal of Research in English Language Teaching), 2024)
This study aims to assess the impact of employing the Global Method on students' reading comprehension at MTsN 5 Jambi City. It adopts a quantitative approach through a quasi-experimental design with non-equivalent control groups. The sample comprises 68 students divided into experimental and control groups selected via purposive random sampling. Data collection involves short-answer questions administered as pre-tests and post-tests. The findings indicate a higher mean post-test score (74.26) compared to the mean pre-test score (49.41). Statistical analysis using the Wilcoxon test reveals a significance level (sig 2-tailed) of 0.000, indicating acceptance of Ha1 (alternative hypothesis) and rejection of H01 (null hypothesis), signifying a significant improvement in students' reading comprehension after implementing the Global Method. Additionally, results from the independent sample t-test show a sig (2-tailed) value of 0.000, with a t-test value (6.074) surpassing the t-table value (1.671) at df = 66, leading to acceptance of Ha2 and rejection of H02. This confirms a significant difference in reading comprehension between students exposed to the Global Method and those who were not.